Perilaku Profesional Dosen Pegawai Negeri Sipil Indonesia - Guspika Guspika (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2009)
The civil servant lecturer professional behavior model was designed based on the social cognitive theory of Bandura (1991,1989,2001) theory of planned behavior (Ajzen, 1988,2005), moral development stages of Kohlberg and ethical decision making model (Jones, 1991; Weber and Gillespie, 1998). The Structural equation analysis result show a fit and goodness of the model with the empirical data i.e; Chi square is only 14,384, probability equal to 0,421, RMSEA is 0,009, GFI is 0,990, AFGI is 0,969, and CMIN/DF is 1,027. The model and empirical data explain that professional behavior of civil servant lecturer in Indonesia at This time is determined by interaction dynamics of: 1) personal factor, i.e. intention to behave professionally, occupational commitment, and organizational commitment; and 2) situational factor, i.e lecturer's response to organizational design. Only around 9,57% of respondents have been successful to demonstrate professional behavior and able to reach "engage in moral behavior"